Governance, vulnerability to climate change, and green growth: International evidence - Thai-ha Le; Youngho Chang; Donghyun Park (Asian Development Bank (ADB), 2016)
We examine the role of governance and vulnerability to climate change in green growth using a global panel data set of 122 countries in 2000.2012. We find that, as expected, governance has a positive effect on environmental performance and vulnerability to climate change has a negative effect. This suggests that promoting good governance and reducing climate change vulnerability can contribute to a cleaner environment. We find qualitatively similar results for the subsample of high-income countries, but governance does not have a significant effect for the subsamples of upper-middleincome, lower-middle-income, and low-income countries. One possible interpretation is that highincome countries have environmental policies which are strong enough to protect the environment, whereas other countries have relatively weak environmental policies which need to be strengthened.
Keywords: Q56; 330; air quality; governance; green growth; PM2.5; vulnerability to climate change